PUPPET AS MEDIA IN IMPROVING YOUNG LEARNERS’ PARTICIPATION IN CONVERSATION - Nabillha, Rinda; Salam, Urai; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This action research is intended to solve the problem of students’ participation in doing conversation in English classroom. The participants were 38 of fifth grade students of SD Muhammadiyah 2 Pontianak. The research showed that puppet as media in improving young learners’ participation in conversation could improve students’ participation from cycle to cycle. The process in three cycles was equal, but there are some differences during the action research including material and problems found. In the first cycle, the research showed the students had participated in conversation. The percentage was 53%, including 11 students asking question, 6 students answering question and 3 students giving opinion. In the second cycle, the students’ participation shows the percentage 61%, including 14 students asking question, 8 students answering question and 4 students giving opinion. Last, in the third cycle, the percentage of students participation shows 74%, including 14 students asking question, 11 students answering question and 5 students giving opinion. To sum up, among two previous cycles, cycle number three had better improvement because more students participated in asking questions, answering questions and giving opinions relevant to the material. Keywords : Puppet, Young learners, Participation Abstark : Penelitian tindakan kelas ini bertujuan untuk menyelesaikan masalah tentang partisipasi siswa dalam melakukan percakapan bahasa inggris di dalam kelas. Partisipan dalam penelitian ini adalah 38 siswa kelas 5 dari SD muhammadiyah 2 Pontianak. Penelitian ini menunjukan bahwa boneka sebagai media untuk meningkatkan partisipasi siswa dalam percakapn bisa meningkatkan partisipasi siswa dalam setiap siklus. Proses dalam tiga siklus sama, tapi terdapat beberapa perbedaan selama melakukan penelitian tindakan kelas meliputi materi dan masalah yang di temukan selama penelitian. Di siklus pertama, penelitian menunjukan siswa telah berpartisipasi dalam percakapan. Persentase dalam siklus pertama 53 %, meliputi 11 siswa bertanya, 6 siswa menjawab dan 3 siswa memberikan pendapat. Dalam siklus kedua, partisipasi siswa menunjukan 61%, meliputi 14 siswa mengajukan pertanyaan, 8 siswa menjawab pertanyaan, dan 4 siswa memberikan pendapat. Terakhir, dalam siklus ketiga persentase partispasi siswa menunjukan 74 %, meliputi 14 siswa bertanya, 11 siswa menjawab pertanyaan, dan 5 siswa memberikan pendapat. Kesimpulannya, `antara 2 siklus sebelumnya, siklus ke tiga peningkatan yang sangat baik karena siswa lebih berpartisipasi dalam bertanya, menjawab pertanyaan dan memberikan pendapat bersangkutan dengan materi . Kata kunci : Boneka, Anak-anak, Partisipasi